Silver and Copper Nanoparticles in Advanced Wound Dressings for Chronic Venous Leg Ulcers: A Critical Clinical Review of Antibacterial Efficacy and Cytotoxicity - Kabat, Jan; Nejc, Wojciech; Walczak, Paulina; Laskus, Justyna; Baida, Maria; Cabaj, Marta; Laskowska, Kinga Elżbieta; Węglarczyk, Zuzanna; Pasik- Gawryluk, Magdalena; Żebrowska, Julia; et al. (Quality in Sport, 2026)
Background. Chronic venous leg ulcers (CVLUs) are a prevalent and clinically challenging condition, frequently complicated by polymicrobial biofilm infections that impair healing. Silver nanoparticles (AgNPs) and copper nanoparticles (CuNPs) have emerged as promising antimicrobial agents for incorporation into advanced wound dressings. Aim. This clinical review critically evaluates and compares the antibacterial efficacy and cytotoxic profiles of AgNPs and CuNPs in the context of chronic venous leg ulcer management. Material and methods. A narrative review of peer-reviewed literature was conducted using PubMed/MEDLINE (2015–2025). Results. Both AgNPs and CuNPs demonstrate comparable broad-spectrum antibacterial and anti-biofilm activity, including against multidrug-resistant organisms. CuNPs additionally exhibit pro-angiogenic and collagen-stimulating properties. Both nanoparticle types show dose-dependent cytotoxicity toward keratinocytes and fibroblasts, with safety thresholds remaining incompletely defined. Conclusions. AgNPs and CuNPs represent therapeutically comparable options for chronic venous leg ulcer management. Standardised clinical trials are needed to establish safe concentration ranges and optimal dressing formulations.